Investigation of temperature effect on magnetic characteristics of manganese-zinc ferrites - Кахняж, Мачей Люцианович; Салах, Яцек Люцианович; Шевчик, Роман Юзевич; Беньковски, Адам Викторович; Коробийчук, Игорь Вацлавович (Eastern-European Journal of Enterprise Technologies, 2015)
The results of investigating the temperature effect on the characteristics of the soft magnetic crystalline materials were presented. Four manganese-zinc ferrites having different compositions of manganese and zinc were examined. The materials studied were shaped as ring cores with a closed magnetic circuit. Each core was wound with the magnetization winding and the measuring winding. Each sample thus created was installed in a cryostat, which was used for stabilizing a predetermined temperature. The magnetic characteristics were measured by a computer-controlled measuring system. The research results indicated a significant relationship between the temperature and magnetic properties of manganese-zinc ferrite. Temperature increase led to lower values of all the parameters of the hysteresis loop: the coercive field, the induction of the residual magnetization and the maximum induction. At low temperatures below 0°C, the maximum induction reached its highest values: 450 T in the sample N41, 370 T in the sample F3001, 360 T in the sample F807, 440 T in the sample T38, and at higher temperatures, the induction began to decrease. The described phenomenon may find practical use in the manufacture of temperature sensors.